Strategies To Reduce The Psychological Burden Of Health Outbreak Based On Experiences During The COVID-19 Pandemic Among Hospital Midwives - Felipe-Dimog, Eva; Liang, Fu-Wen; Tumulak, Ma‑Am Joy; Fomocao, Alfred O.; Efendi, Ferry (Jurnal Keperawatan Muhammadiyah, 2024)
Coronavirus disease 2019 (COVID-19) was a public health outbreak that caused significant psychological difficulties for healthcare workers worldwide, including hospital midwives. As a result, strategies to reduce the psychological burden during health outbreaks based on hospital midwives' experiences during the COVID-19 pandemic are critical. The goal of this perspective paper was to present some strategies for reducing the negative psychological effects of a health outbreak based on hospital midwives' experiences during the COVID-19 pandemic. Few sources reviewed demonstrated that hospital midwives felt overwhelmed at work and experienced worry and anxiety during the COVID-19 pandemic. Despite these negative consequences, hospital midwives were glad to have developed interpersonal relationships with other health providers and patients as a result of the collaborative effort put in during the COVID-19 pandemic management. Literature suggests that reorganizing the maternity care system, providing adequate supplies, providing strong support, and improving information sharing are among the strategies to lessen the psychological burden during health outbreaks. The pandemic had a negative psychological impact on hospital midwives, which requires attention. Implementing coping strategies to lessen the psychological burden among hospital midwives during health outbreaks contribute to a better provision of healthcare during health emergencies.